Long shore sediment transport computation for Hai Hau beach-Nam Dinh province - Hung, Nguyen Manh (Vietnam Journal of Mechanics, 2003)
Several stretches of shore line in the Red River Delta (RRD) are suffering from severe erosion, especially an area between too large river mouths Balat in the North and Day in the South, known as Hai Hau beach. Several different hypothesis have been put forward to explain this erosion. The cut off of the Ha Lan river mouth (in 1955) which discharged sediment at the upstream end of the beach, possibly affects Hai Hau beach. Also, the construction of Hoa Binh dam in the upstream part of Red river has reduced the sediment supply to the area. In this study, it is shown that the prevailing wave climate in connection with the complex topography of Balat river mouth and Hai Hau beach promotes erosion along the coastal line. A two dimensional random wave transformation model was used with 20-year time series of hindcast waves to compute the long shore sediment transport along the study beach.